Protease inhibition and absorption enhancement by functional nanoparticles for effective oral insulin delivery - Su, Fang-Yi; Lin, Kun-Ju; Sonaje, Kiran; Wey, Shiaw-Pyng; Yen, Tzu-Chen; Ho, Yi-Cheng; Panda, Nilendu; Chuang, Er-Yuan; Maiti, Barnali; Sung, Hsing-Wen (Biomaterials, 2012)
Complexing agents such as diethylene triamine pentaacetic acid (DTPA) are known to disrupt intestinal tight junctions and inhibit intestinal proteases by chelating divalent metal ions. This study attempts to incorporate these benefits of DTPA in functional nanoparticles (NPs) for oral insulin delivery. To maintain the complexing agent concentrated on the intestinal mucosal surface, where the paracellular permeation enhancement and enzyme inhibition are required, DTPA was covalently conjugated on poly(γ-glutamic acid) (γPGA). The functional NPs were prepared by mixing cationic chitosan (CS) with anionic γPGA-DTPA conjugate. The γPGA-DTPA conjugate inhibited the intestinal proteases substantially, and produced a transient and reversible enhancement of paracellular permeability. The prepared NPs were pH-responsive; with an increasing pH, CS/γPGA-DTPA NPs swelled gradually and disintegrated at a pH value above 7.0. Additionally, the biodistribution of insulin orally delivered by CS/γPGA-DTPA NPs in rats was examined by confocal microscopy and scintigraphy. Experimental results indicate that CS/γPGA-DTPA NPs can promote the insulin absorption throughout the entire small intestine; the absorbed insulin was clearly identified in the kidney and bladder. In addition to producing a prolonged reduction in blood glucose levels, the oral intake of the enteric-coated capsule containing CS/γPGA-DTPA NPs showed a maximum insulin concentration at 4 h after treatment. The relative oral bioavailability of insulin was approximately 20%. Results of this study demonstrate the potential role for the proposed formulation in delivering therapeutic proteins by oral route.